Mortality Outcomes and Predictors of Failed Thrombolysis following STEMI Thrombolysis in a Non-PCI Capable Tertiary Hospital - AHMED, ADEEL; ALI, RIMSHA; FARID, GHULAM; SAQIB, AHMAD; ALI, MUHAMMAD; MUNEEB, MUHAMMAD; AKRAM, ZOHAIB (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Thrombolysis is an essential treatment for ST elevation myocardial infarction (STEMI) in situations where primary percutaneous coronary intervention (PCI) is unavailable. This research examines mortality outcomes and determines predictors of unsuccessful thrombolysis in a tertiary hospital lacking PCI capabilities. Methods: A retrospective analysis was conducted on 550 patients who received thrombolysis following STEMI at a non-PCI capable tertiary hospital from 2018 to 2023. Patient data, including demographics, clinical presentation, treatment protocols, and outcomes, were reviewed. Failed thrombolysis was defined as the absence of >50% resolution of ST-segment elevation within 90 minutes post-thrombolysis. Multivariate logistic regression analysis was used to identify predictors of failed thrombolysis. Results: The mean age of the patients was 60 ± 10 years, with 70% being male. Thrombolysis was successful in 75% of cases, while 25% (138 patients) experienced failed thrombolysis. The in-hospital mortality rate was 12% for the overall cohort, but significantly higher at 30% among those with failed thrombolysis. Predictors of failed thrombolysis included advanced age (>65 years), delayed presentation (>6 hours from symptom onset), anterior infarction, and higher Killip class at presentation (III-IV). Multivariate analysis identified delayed presentation (OR 2.5, 95% CI 1.7-3.7) and anterior infarction (OR 3.1, 95% CI 2.1-4.5) as the strongest predictors of failed thrombolysis. Conclusion: Failed thrombolysis following STEMI is associated with significantly higher mortality in a non-PCI capable tertiary hospital setting. Delayed presentation and anterior infarction are key predictors of thrombolysis failure, highlighting the need for early intervention and potential transfer to PCI-capable centers.